Assessment of Woody Residual Biomass Generation Capacity in the Central Region of Portugal: Analysis of the Power Production Potential - Nunes, Leonel J.R. (2022)
Biomass is an alternative energy source with high potential to contribute to the global energy mix and to countries’ energetic independence. The case of Portugal is particularly relevant, given its biomass availability. Thus, the quantification of woody residual biomass is assumed to be urgent. To achieve the objective of quantifying residual woody biomass, various available data were used, namely the Land Cover and Soil Use Map (COS 2018), from which areas occupied by different categories were selected as being the most relevant. Then, based on coefficients previously established, the amounts of residual woody biomass were determined, namely for maritime pine forests, eucalyptus forests, scrubland, vineyards, olive groves, and orchards. Then, the potential for generating electricity was estimated. It was found that for the hypothetical scenario of the total conversion of the recently closed Pêgo coal power plant to biomass, the available amounts of residual woody biomass in the country would not be sufficient to ensure the operation. On the other hand, if the power plant only worked as a backup unit, the available quantities could ensure its operation and contribute to creating a value chain for residual woody biomass of forest and agricultural origin within a circular economy and sustainable development approach